Look Who’s Asking—Reflections on Participatory and Transdisciplinary Marine Research Approaches - Breckwoldt, Annette; Lopes, Priscila F. M.; Selim, Samiya A. (Frontiers in Marine Science, 2021)
Marine conservation transdisciplinary researchers often get to the field with a previously designed question, often formulated outside the actual geographical, social, cultural and ecological setting in which the research projects are supposed to be anchored. Involving people on the ground in the initial phase of formulating the questions and setting the research agenda is still uncommon. Once in the field, transdisciplinary researchers may or may not have the support of local communities to sample their data, although they will regularly need to count on these same communities if a collaborative regime is to be pursued and informed by the research outcome. This paper discusses measures that can be taken by marine fisheries and marine conservation researchers to improve participation in, and ownership of, the research by local counterparts, most importantly members of the communities where research is being conducted. The data was generated with a purposively sampled survey of 18 members of our research networks. Key proposed measures derived from this data include: (1) build rapport; (2) engage and exchange; (3) be accommodating and attentive; and (4) be respectful. Knowing who is asking the questions and assuring that all stakeholders have a voice in this process becomes especially relevant under extreme circumstances (e.g., disasters, pandemics), when problems are numerous but can only be accessed by those on the ground. We advise for faster progress in transforming academic and funding environments for true “level-playing-field” transdisciplinary and co-designed research projects that can help change top-down research tendencies.